INTERACTIVE GAMES AND DIGITAL TOOLS IN DEVELOPING COMMUNICATIVE COMPETENCE IN ENGLISH LESSONS: IN THE EXAMPLE OF 8TH–9TH GRADE STUDENTS - Beknazarova Nigina Abdiqodir qizi; Madiyeva Madina Yusupovna (Modern American Journals, 2025)
In English language teaching, interactive games and digital tools play a transformative role in enhancing communicative competence. This paper explores how technology-integrated methods foster active language use, student engagement, and collaborative learning. Drawing on current research and practical classroom applications, it examines the effectiveness of various digital resources such as educational games, apps, and virtual platforms in developing learners’ speaking, listening, reading, and writing skills. The study underscores the importance of integrating meaningful, context-driven activities that simulate real-life communication, thereby supporting a learner-centered approach to language education.
Keywords: Communicative competence, English language teaching, digital tools, interactive games, language learning, student engagement, educational technology.